2015
DOI: 10.14742/ajet.1668
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the intention to use technology for teaching mathematics among pre-service teachers in Serbia

Abstract: This study aims to examine the variables that influence Serbian pre-service teachers' intention to use technology to teach mathematics. Using the technology acceptance model (TAM) as the framework, we developed a research model to include subjective norm, knowledge of mathematics, and facilitating conditions as external variables to the TAM. In addition, we investigated the influence of gender and age on the behavioural intention to use technology. With data gathered from 313 participants using a survey questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 46 publications
7
65
2
Order By: Relevance
“…Consistent with past research (e.g. Teo & Milutinović, 2015;Cheung & Vogel, 2013;Edmunds, Thorpe, & Conole, 2012;Pynoo et al, 2012;Wong, 2015), almost all of the hypotheses that used TAM variables to determine pre-service teachers' intentions to use technology in teaching mathematics were supported for both traditional and innovative uses of technology. This means that when Serbian pre-service teachers find technology useful and easy to use, they are more positive towards the use of technology, and these positive feelings in turn lead to a higher tendency to adopt computers at any level in the teaching of mathematics.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with past research (e.g. Teo & Milutinović, 2015;Cheung & Vogel, 2013;Edmunds, Thorpe, & Conole, 2012;Pynoo et al, 2012;Wong, 2015), almost all of the hypotheses that used TAM variables to determine pre-service teachers' intentions to use technology in teaching mathematics were supported for both traditional and innovative uses of technology. This means that when Serbian pre-service teachers find technology useful and easy to use, they are more positive towards the use of technology, and these positive feelings in turn lead to a higher tendency to adopt computers at any level in the teaching of mathematics.…”
Section: Discussionsupporting
confidence: 81%
“…Further, both perceived usefulness (Teo, 2011) and perceived ease of use (Teo et al, 2009) have been shown to influence attitudes towards technology (Teo & Milutinović, 2015;Teo, Milutinović, & Zhou, 2016;Wong, 2015). Additionally, perceived ease of use has been found to predict perceived usefulness (Teo, 2011;Teo & Milutinović, 2015;Teo, Lee, & Chai, 2008;Wong, 2015) and behavioural intention to use technology (Saadé & Bahli, 2005). Thus, we formulated the following hypotheses: H1: Pre-service teachers' perceptions about the usefulness of technology have a significant influence on their attitude toward computer use in teaching mathematics.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Looking at the two profiles it is clear that some pre-service teachers are intrinsically motivated to use ICT in their educational practice, while others do not share this affinity (e.g., Teo & Milutinovic, 2015). For this reason, many researchers placed the individual teacher at the centre of educational change processes (Stoll, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Some pre-service teachers are intrinsically motivated to use ICT in educational practice, while others do not share this affinity. For this reason, many researchers have centred on critical individual characteristics associated with TPACK, such as pre-service teachers' attitudes (e.g., Holland & Piper, 2016), ease of use (e.g., Teo & Milutinovic, 2015), and their self-efficacy (e.g., Abbitt, 2011;. But a mere focus on pre-service teachers' characteristics could lead to individual blame rather than system blame when focusing on explaining variables related to TPACK.…”
Section: Introductionmentioning
confidence: 99%